Aspects of Algerian Medical Translation - BENCHABANE, Nassima (Journal of Human Sciences, 2015)
The aim of this article is to throw light on some aspects of the English-Arabic Medical translation which belong to the most significant area of difficulty met by the Algerian university students, especially in terms of style and terminology. It also attempts to draw attention to some Algerian students’ misconceptions related to the translation of English Medical texts into Arabic.